Grain Quality Research of Rice for Ensuring Nutritional Food Security - Shozib, HB; Siddiquee, MA; Rahman, NMF; Mamun, MAA; Sarkar, MAR; Rabbi, SMHA; Salam, MU; Kabir, MS (Bangladesh Rice Journal, 2021)
Per capita rice consumption in Bangladesh is in a decreasing trend. Considering the constant loss of per capita daily dietary energy @ 0.028% year-1, nutrition-based prediction of daily dietary energy intake (kcal) may be reduced to 2201 and 2188 kcal for our population by 2030 and 2050, respectively. We are optimistic that consuming per capita rice consumption of 365 g and 363 g (dry wt. basis) in 2030 and 2050, respectively will help to attain the current trends of 59.0% of Calorie intake from rice only. Appro-priate amount of rice intake including incorporating rice-based products in our daily diet, we will able to attain daily required dietary allowance and combination of both may ensure nutritional security along with food security in Bangladesh in a way to effective utilization of the rice grain. Rice is nutraceu-tically enriched because of the presence of phenolic compounds, flavonoids and antioxidants. Research thrust of BRRI is to focus on releasing nutraceutically enriched HYVs such as high zinc, high iron, beta carotene (A Vit A precursor) enriched antioxidant rice etc. Gluten free rice-based bakery products have potential to get popularize in Bangladeshi population with ensuring high nutritional value and effective management of controlling non-communicable diseases since lesser amount of rice carbohydrates are being utilized in formulating products such as rice biscuit, rice cake etc. BRRI has formulated gluten free rice-based energy dense product specially rice biscuit (ED 5.15) could be extended as a potential nutri-tionally balanced dry food application in malnutrition mitigation programme, school feeding nutritional programme and humanitarian relief operation replacing current wheat-based products. Bangladesh Rice J. 24 (2): 103-117, 2021